Pengaruh Keterampilan Karyawan dan Kualitas Pelayanan terhadap Kepuasan Pelanggan pada PT Mayindo Tritunggal - Allyssia Rorencia; Lela Elvira; Maria Lapriska Dian Ela Revita (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
PT Mayindo Tritunggal is a company operating in the beauty service industry. In the face of increasingly intense competition in the service sector, the company needs to improve customer satisfaction through optimal employee skills and service quality. This study aims to analyze the influence of employee skills and service quality on customer satisfaction at PT Mayindo Tritunggal. This research employed a quantitative approach using multiple linear regression analysis with IBM SPSS Statistics version 20. The study involved 50 respondents selected using a non-probability sampling technique. Primary data were collected through questionnaires distributed to customers, while secondary data were obtained from books, journals, and the company's official website. The results indicate that employee skills have a positive and significant effect on customer satisfaction, with a t-value of 3.766 > 2.011 and a significance value of 0.000 < 0.05. Service quality also has a positive and significant effect on customer satisfaction, with a t-value of 6.048 > 2.011 and a significance value of 0.000 < 0.05. Simultaneously, employee skills and service quality have a positive and significant effect on customer satisfaction, with an F-value of 21.307 > 3.20 and a significance value of 0.000 < 0.05. The Adjusted R Square value of 0.453 indicates that employee skills and service quality explain 45.3% of the variation in customer satisfaction, while the remaining 54.7% is influenced by other factors outside the scope of this study. Therefore, employee skills and service quality have been proven to have a positive and significant influence, both partially and simultaneously, on customer satisfaction at PT Mayindo Tritunggal